Chloroprene polymer, chloroprene polymer latex, method for producing chloroprene polymer latex, compound composition, and vulcanized molded product

JP7633381B2Active Publication Date: 2025-02-19DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023511125
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-24
Publication Date
2025-02-19
Estimated Expiration
2042-03-24

AI Technical Summary

Benefits of technology

【0010】 本発明に係るクロロプレン系重合体によれば、動的耐久疲労性に優れる加硫成形体を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633381000001
    Figure 0007633381000001
  • Figure 0007633381000002
    Figure 0007633381000002
  • Figure 0007633381000003
    Figure 0007633381000003
Patent Text Reader

Abstract

The present invention provides: a chloroprene polymer and a chloroprene polymer latex, each of which enables the achievement of a vulcanization molded body that has excellent dynamic endurance fatigue properties; a compound composition and a vulcanization molded body, each of which contains this chloroprene polymer; and a method for producing one of these products. The present invention provides a chloroprene polymer which is configured such that, with respect to the 1H-NMR spectrum thereof as determined in a deuterated chloroform solvent, there is a peak at 5.80 to 6.00 ppm; if A is the peak area of 5.80 to 6.00 ppm and B is the peak area of 4.05 to 6.10 ppm, A / B is 1.20 / 100 or less; there is a peak at 5.40 to 5.60 ppm; and if D is the peak area of 5.40 to 5.60 ppm and B is the peak area of 4.05 to 6.10 ppm, D / B is 97.20 / 100 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chloroprene polymer, a chloroprene polymer latex, a method for producing a chloroprene polymer latex, a compound composition, and a vulcanized molded article. [Background technology]

[0002] Chloroprene rubber has excellent heat resistance, weather resistance, ozone resistance, chemical resistance, flame retardancy, etc., and is easy to process, so it is widely used as a raw material for various automotive parts and industrial rubber parts such as belts, hoses, anti-vibration rubber, etc. Furthermore, there is a constant demand for improved durability and reliability of these products.

[0003] For example, Patent Document 1 discloses a xanthogen-modified chloroprene rubber having a bonding amount of chloroprene units of 78 to 98.9 mass%, a bonding amount of 2,3-dichloro-1,3-butadiene units of 1 to 20 mass%, a bonding amount of α,β-unsaturated carboxylic acid units of 0.1 to 2 mass%, and a weight average molecular weight of 340,000 to 520,000. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 110369 Summary of the Invention [Problem to be solved by the invention]

[0005] However, conventional chloroprene polymers have a problem in that the dynamic fatigue durability of vulcanized molded articles containing the chloroprene polymers is insufficient.

[0006] The present invention has been made in view of the above circumstances, and provides a chloroprene polymer, a chloroprene polymer latex, a compound composition containing such a chloroprene polymer, and a vulcanized molded article, which can give a vulcanized molded article having excellent dynamic fatigue durability, as well as methods for producing these. [Means for solving the problem]

[0007] According to the present invention, a chloroprene-based polymer is measured in a deuterated chloroform solvent. 1 The chloroprene polymer has a peak at 5.80 to 6.00 ppm in a H-NMR spectrum, and when the peak area from 5.80 to 6.00 ppm is defined as A and the peak area from 4.05 to 6.10 ppm is defined as B, A / B is 1.20 / 100 or less; and has a peak at 5.40 to 5.60 ppm, and when the peak area from 5.40 to 5.60 ppm is defined as D and the peak area from 4.05 to 6.10 ppm is defined as B, D / B is 97.20 / 100 or less.

[0008] The present inventors have conducted extensive research and found that the 1 The present inventors have found that a chloroprene polymer can be obtained from a vulcanized molded product having excellent dynamic fatigue durability by adjusting the peak area ratio of a peak observed at a specific position in a H-NMR spectrum to fall within a specific numerical range, and have thus completed the present invention.

[0009] Various embodiments of the present invention will be described below. The embodiments described below can be combined with each other. Preferably, the measurement is performed in deuterated chloroform solvent. 1 In the H-NMR spectrum, it has a peak at 4.15 to 4.20 ppm, and when the peak area from 4.15 to 4.20 ppm is defined as C and the peak area from 4.05 to 6.10 ppm is defined as B, C / B is 0.10 / 100 or more. The chloroprene polymer described above is preferably for use in a vulcanized molded article. According to another aspect of the present invention, there is provided a chloroprene polymer latex containing the above-described chloroprene polymer, characterized in that an amount of substance of an alkali metal cation in the chloroprene polymer latex per unit mass is 0.05 to 0.12 mmol / g, and a rosin acid amount measured by gas chromatography after refluxing an ethanol-toluene azeotropic mixture soluble matter defined in JIS K 6229 in a solid matter containing a chloroprene polymer obtained by freeze-drying the chloroprene polymer latex and treating the obtained extract with hydrochloric acid is 1.4 to 3.2 mass% based on 100 mass% of the chloroprene polymer. According to another aspect of the present invention, there is provided a method for producing the chloroprene polymer latex described above, comprising: an emulsion polymerization step of emulsion-polymerizing a monomer including a chloroprene monomer; and in the emulsion polymerization step, 1.2 to 2.2 parts by mass of a rosin acid salt is used relative to 100 parts by mass of the total of the chloroprene monomer and the monomer copolymerizable with chloroprene, and a total amount of sodium hydroxide and potassium hydroxide is 0.1 to 0.5 parts by mass relative to 100 parts by mass of an aqueous medium. A method for producing a chloroprene-based polymer latex is provided. According to another aspect of the present invention, there is provided a compound composition comprising the above-described chloroprene polymer. There is also provided a vulcanized molded article made from the above-mentioned compound composition. Effect of the Invention

[0010] According to the chloroprene polymer of the present invention, a vulcanized molded article having excellent dynamic fatigue resistance can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below by illustrating the embodiments of the present invention. The present invention is not limited by these descriptions. The various features of the embodiments of the present invention shown below can be combined with each other. In addition, each feature can be an invention independently.

[0012] 1. Chloroprene polymers The chloroprene polymer according to the present invention is a homopolymer of 2-chloro-1,3-butadiene (hereinafter, referred to as chloroprene) or a copolymer of a chloroprene monomer and another monomer copolymerizable therewith.

[0013] Examples of monomers copolymerizable with chloroprene monomers include 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, acrylic acid or esters thereof, and methacrylic acid or esters thereof. These may be used alone or in combination of two or more. Although not particularly limited, from the viewpoint of maintaining the properties derived from chloroprene, the chloroprene-based polymer according to one embodiment of the present invention preferably has 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more of monomer units derived from chloroprene monomers when the chloroprene-based polymer is taken as 100% by mass.

[0014] The chloroprene-based polymer according to one embodiment of the present invention is measured in a deuterated chloroform solvent. 1 In the H-NMR spectrum, the chloroprene polymer according to one embodiment of the present invention has a peak at 5.80 to 6.00 ppm, where A is the peak area at 5.80 to 6.00 ppm and B is the peak area at 4.05 to 6.10 ppm, and A / B is 1.20 / 100 or less. A / B can be, for example, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20 / 100, or may be within a range between any two of the values ​​exemplified here.

[0015] 1The H-NMR spectrum is measured by purifying a chloroprene polymer with benzene and methanol, freeze-drying the sample, and dissolving it in deuterated chloroform. The peak position is based on the peak of chloroform in deuterated chloroform (7.24 ppm).

[0016] In addition, 1 The peak appearing at 5.80 to 6.00 ppm in the H-NMR spectrum is presumed to be related to the structure represented by the following formula (1).

[0017] [ka]

[0018] It is presumed that the chloroprene-based polymer according to one embodiment of the present invention is a chloroprene-based polymer from which a vulcanized molded product having excellent dynamic fatigue durability can be obtained by setting A / B to the above-mentioned upper limit or less and appropriately controlling the amount of structures that can become crosslinking points.

[0019] The chloroprene-based polymer according to one embodiment of the present invention is measured in a deuterated chloroform solvent. 1 In the H-NMR spectrum, the chloroprene polymer according to one embodiment of the present invention has a peak at 5.40 to 5.60 ppm, where D is the peak area at 5.40 to 5.60 ppm and B is the peak area at 4.05 to 6.10 ppm, and D / B is preferably 97.20 / 100 or less, more preferably 97.18 / 100 or less, and even more preferably 97.15 / 100 or less. D / B can be, for example, 97.00, 97.01, 97.02, 97.03, 97.04, 97.05, 97.06, 97.07, 97.08, 97.09, 97.10, 97.11, 97.12, 97.13, 97.14, 97.15, 97.16, 97.17, 97.18, 97.19, 97.20 / 100, or may be within a range between any two of the values ​​exemplified here.

[0020] Also, 1The peak appearing at 5.40 to 5.60 ppm in the H-NMR spectrum is presumed to be related to the structure represented by the following formula (2).

[0021] [ka]

[0022] By setting D / B to the above upper limit or less, the rubber properties of the obtained vulcanized molded article can be maintained, and in particular, the rubber can be prevented from becoming too hard. In the past, attempts have been made to adjust the content of the microstructure of a chloroprene polymer, for example, by adjusting the temperature during polymerization of the chloroprene polymer or by heat-treating the chloroprene polymer. However, in the conventional method such as heat-treating the chloroprene polymer, when the amount of the structure represented by formula (1) corresponding to A / B that can be a crosslinking point is reduced, the amount of the structure represented by formula (2) corresponding to D / B increases at the same time, and it has been difficult to highly adjust the content of the microstructure of the chloroprene polymer, particularly to reduce the amount of the structure represented by formula (1) corresponding to A / B that can be a crosslinking point while suppressing the increase in the amount of the structure represented by formula (2) corresponding to D / B. However, according to the present invention, it is presumed that the amount of the structure represented by formula (1) corresponding to A / B, which can serve as a crosslinking point, can be reduced without increasing the amount of the structure represented by formula (2) corresponding to D / B by highly adjusting the production conditions for the chloroprene polymer, in particular the amounts of the rosin acid salt, sodium hydroxide, and potassium hydroxide charged during polymerization of the chloroprene polymer, resulting in a chloroprene polymer from which a vulcanized molded product having excellent dynamic fatigue durability can be obtained.

[0023] The chloroprene-based polymer according to one embodiment of the present invention is measured in a deuterated chloroform solvent. 1In the H-NMR spectrum, it has a peak at 4.15 to 4.20 ppm. In addition, in the chloroprene polymer according to one embodiment of the present invention, when the peak area at 4.15 to 4.20 ppm is C and the peak area at 4.05 to 6.10 ppm is B, it is preferable that C / B is 0.10 / 100 or more. There is no particular upper limit, but it is, for example, 1.000 / 100 or less. C / B can be, for example, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, or 1.00, and may be within a range between any two of the numerical values ​​exemplified here.

[0024] In addition, 1 The peak appearing at 4.15 to 4.20 ppm in the H-NMR spectrum is presumed to be associated with the 1,2-OH rearrangement structure represented by the following formula.

[0025] [ka]

[0026] In the chloroprene polymer according to one embodiment of the present invention, the amount of the structure represented by formula (1) corresponding to A / B that can serve as a crosslinking point can be reduced without increasing the amount of the structure represented by formula (2) corresponding to D / B by highly adjusting the production conditions of the chloroprene polymer, in particular the amounts of the rosin acid salt, sodium hydroxide, and potassium hydroxide charged during polymerization of the chloroprene polymer, and in this case, the amount of the structure represented by formula (3) corresponding to C / B may be increased compared to conventional chloroprene polymers. It is presumed that the chloroprene polymer according to one embodiment of the present invention, which has D / B, A / B, and C / B within the above-mentioned numerical ranges, is a chloroprene polymer from which a vulcanized molded product having better dynamic fatigue durability can be obtained. From the viewpoint of having the above-mentioned properties, the chloroprene polymer according to one embodiment of the present invention is preferably used for vulcanized molded products.

[0027] 2. Chloroprene polymer latex The chloroprene polymer latex according to the present invention contains the above-mentioned chloroprene polymer, and it is preferable that the amount of alkali metal cation in the chloroprene polymer latex and the amount of rosin acid contained in the chloroprene polymer are within specific numerical ranges.

[0028] 2.1 Alkali metal cations The chloroprene polymer latex according to the present invention preferably has an amount of alkali metal cation per unit mass of 0.05 to 0.12 mmol / g. The amount of alkali metal cation may be, for example, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, or 0.12 mmol / g, and may be within a range between any two of the values ​​exemplified here. The amount of alkali metal cations in the chloroprene polymer latex can be quantified by acid decomposing the chloroprene polymer latex with sulfuric acid or nitric acid, acidifying it with hydrochloric acid, and then analyzing it with an inductively coupled plasma atomic emission spectrometer. Specifically, the amount of alkali metal cations in the chloroprene polymer latex can be determined by the method described in the Examples.

[0029] In one embodiment of the present invention, the alkali metal cations are preferably potassium ions and sodium ions.

[0030] 2.2 Rosin acid In the chloroprene polymer latex according to the present invention, the chloroprene polymer-containing solid content obtained by freeze-drying the chloroprene polymer latex is preferably subjected to reflux extraction of an ethanol-toluene azeotrope soluble matter defined in JIS K 6229, and the resulting extract is treated with hydrochloric acid, and then the amount of rosin acid measured by gas chromatography is preferably 1.4 to 3.2% by mass relative to 100% by mass of the chloroprene polymer contained in the solid content. The amount of rosin acid in the chloroprene polymer-containing solid content may be, for example, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, or 3.2% by mass, or may be within a range between any two of the numerical values ​​exemplified here. The amount of rosin acid in the solid content containing a chloroprene polymer can be determined by extracting rosin acids from the solid content containing a chloroprene polymer obtained by freeze-drying a chloroprene polymer latex with an ethanol-toluene azeotropic mixture (ethanol / toluene volume ratio of 7 / 3 (ETA)) and measuring the amount by gas chromatography; specifically, the amount can be determined by the method described in the examples.

[0031] The rosin acid according to one embodiment of the present invention preferably contains a single resin acid component such as abietic acid, dehydroabietic acid, dihydroabietic acid, pimaric acid, dihydropimaric acid, isopimaric acid, secodehydroabietic acid, or a mixture thereof.

[0032] The chloroprene polymer latex according to the present invention becomes a chloroprene polymer capable of giving a vulcanized molded article having superior dynamic fatigue durability by adjusting the amount of alkali metal cation and the amount of rosin acid within the above-mentioned specific numerical ranges.

[0033] In addition, the chloroprene polymer latex according to one embodiment of the present invention may contain a freezing stabilizer, an emulsion stabilizer, a viscosity modifier, an antioxidant, a preservative, etc., within a range that does not impair the effects of the present invention.

[0034] In the chloroprene polymer latex according to one embodiment of the present invention, when the chloroprene polymer contained in the chloroprene polymer latex is taken as 100% by mass, the content of emulsifiers other than emulsifiers containing rosin acid can be 1% by mass or less, and 0.5% by mass or less. Here, examples of emulsifiers other than emulsifiers containing rosin acid include metal salts of aromatic sulfonic acid-formalin condensates, sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium alkyldiphenylethersulfonate, potassium alkyldiphenylethersulfonate, sodium polyoxyethylene alkylethersulfonate, sodium polyoxypropylene alkylethersulfonate, potassium polyoxyethylene alkylethersulfonate, and potassium polyoxypropylene alkylethersulfonate. In the chloroprene polymer latex according to one embodiment of the present invention, the content of metal salts of aromatic sulfonic acid-formalin condensates, for example, the content of naphthalenesulfonic acid-formalin condensates, can be 1% by mass or less, and 0.5% by mass or less.

[0035] 3. Method for producing chloroprene polymer latex The method for producing the chloroprene polymer latex according to the present invention is not particularly limited, but the latex can be obtained by a production method including an emulsion polymerization step of emulsion polymerizing monomers including a chloroprene monomer. In the emulsion polymerization step according to one embodiment of the present invention, a chloroprene monomer or a chloroprene monomer and another monomer copolymerizable therewith is emulsion-polymerized using an appropriate amount of an emulsifier, a dispersant, a catalyst, a chain transfer agent, etc., and when a target polymerization rate is reached, a polymerization terminator is added to obtain a chloroprene polymer latex. From the chloroprene polymer latex thus obtained, unreacted monomers can be removed by a steam flash method, a concentration method, etc.

[0036] <Monomer> The monomers containing the chloroprene monomer include chloroprene monomer and other monomers copolymerizable with the chloroprene monomer described above.

[0037] <Rosin acid salt> In the emulsion polymerization step according to one embodiment of the present invention, it is preferable to use 1.2 to 2.2 parts by mass of a rosin acid salt with respect to 100 parts by mass in total of the chloroprene monomer and the monomer copolymerizable with chloroprene. The amount of the rosin acid salt used can be, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, or 2.2 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. Examples of rosin acid salts include alkali metal salts such as sodium and potassium, alkaline earth metal salts such as calcium, and ammonium salts. It is preferable to use sodium salts or potassium salts from the viewpoint of ease of handling, etc. Furthermore, the rosin acid contained in the rosin acid salt preferably includes the rosin acids exemplified above. In the emulsion polymerization step according to one embodiment of the present invention, rosin acid may be used in combination. When rosin acid is used, the amount of rosin acid used may be, for example, 0.1, 0.2, 0.3, 0.4, or 0.5 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here.

[0038] <Other emulsifiers / dispersants> In the production method according to one embodiment of the present invention, other emulsifiers may be used in combination as necessary for the purpose of stabilizing control of the polymerization reaction. As the other emulsifiers / dispersants, for example, the compounds listed above as emulsifiers other than the emulsifier containing rosin acid can be used. In the production method according to one embodiment of the present invention, the amount of the emulsifier other than the emulsifier containing rosin acid used can be 1% by mass or less, and 0.5% by mass or less, relative to 100 parts by mass in total of the chloroprene monomer and the monomer copolymerizable with chloroprene.

[0039] <Potassium hydroxide and sodium hydroxide> In the emulsion polymerization step according to one embodiment of the present invention, the total amount of sodium hydroxide and potassium hydroxide used is preferably 0.1 to 0.5 parts by mass, and more preferably 0.1 to less than 0.5 parts by mass, per 100 parts by mass of the aqueous medium. The total amount of sodium hydroxide and potassium hydroxide can be, for example, 0.1, 0.2, 0.3, 0.4, or 0.5 parts by mass, and may be within a range between any two of the values ​​exemplified here. As the aqueous medium, it is preferable to use water, and in particular pure water.

[0040] <Polymerization initiator> As the polymerization initiator, potassium persulfate, benzoyl peroxide, ammonium persulfate, hydrogen peroxide, etc., which are used in normal radical polymerization, can be used.

[0041] <Chain transfer agent> The chain transfer agent is not particularly limited as long as it is one that is generally used in the production of chloroprene-based polymers. For example, known chain transfer agents such as long-chain alkyl mercaptans such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-octyl mercaptan, dialkyl xanthogen disulfides such as diisopropyl xanthogen disulfide and diethyl xanthogen disulfide, and iodoform can be used.

[0042] <Polymerization temperature> The polymerization temperature is preferably in the range of 0 to 55° C. from the viewpoint of ease of reaction control, etc. In order to carry out the polymerization reaction more smoothly and safely, it is preferable that the lower limit of the polymerization temperature is 10° C. or more and the upper limit is 45° C. or less.

[0043] <Polymerization conversion rate> The polymerization conversion rate can be in the range of 60 to 95%. The polymerization reaction can be terminated by adding a polymerization terminator. By keeping the polymerization conversion rate within the above numerical range, the formation of gel can be suppressed.

[0044] <Polymerization terminator> As the polymerization terminator, for example, thiodiphenylamine, 4-tert-butylcatechol, 2,2'-methylenebis-4-methyl-6-tert-butylphenol, etc. can be used. Unreacted monomers after the completion of emulsion polymerization can be removed by a conventional method such as reduced pressure distillation.

[0045] The method for producing a chloroprene polymer latex according to one embodiment of the present invention preferably does not include a step of heating at 140° C. or higher for 1 hour or more, and more preferably does not include a step of heating at 140° C. or higher. The method for producing a chloroprene polymer latex according to one embodiment of the present invention preferably does not include a step of heating at 55° C. or higher for 3 hours or more, and more preferably does not include a step of heating at 55° C. or higher for 1 hour or more. According to the production method of one embodiment of the present invention, by precisely adjusting the production conditions of the chloroprene polymer, for example, the amounts of a rosin acid salt, sodium hydroxide, and potassium hydroxide charged during polymerization of the chloroprene polymer, it is possible to more precisely control the microstructure of the chloroprene polymer without the heating step or even if the heating step is performed at a lower temperature or for a shorter time than in the past, and a chloroprene polymer can be obtained from which a vulcanized molded product having better dynamic fatigue durability than in the past can be obtained.

[0046] 4. Method for producing chloroprene polymer The chloroprene polymer according to the present invention can be obtained by drying up the above-mentioned chloroprene polymer latex. The drying up is carried out by a known method.

[0047] 5. Compound composition and vulcanized molded body The compound composition according to the present invention contains the above-mentioned chloroprene polymer latex or chloroprene polymer, and the vulcanized molded article according to the present invention is obtained by vulcanizing the above-mentioned compound composition.

[0048] The compound composition according to one embodiment of the present invention may contain, in addition to the above-mentioned chloroprene polymer latex or chloroprene polymer, for example, a vulcanizing agent, a vulcanization accelerator, a filler or reinforcing agent, a plasticizer, a processing aid and a lubricant, an antiaging agent, and a silane coupling agent.

[0049] <Vulcanizing agent> The type of vulcanizing agent is not particularly limited as long as it does not impair the effects of the present invention, and one or more of ordinary vulcanizing agents that can be used for chloroprene rubber can be freely selected and used. Examples of vulcanizing agents include zinc oxide, magnesium oxide, lead oxide, lead tetroxide, iron trioxide, titanium dioxide, calcium oxide, and hydrotalcite. The amount of vulcanizing agent is also not particularly limited. In the compound composition according to one embodiment of the present invention, the amount of vulcanizing agent is preferably 3 to 15 parts by mass per 100 parts by mass of the chloroprene polymer. If the vulcanizing agent is added within this range, processing safety is ensured and a good vulcanized product can be obtained.

[0050] <Vulcanization accelerator> The compound composition according to one embodiment of the present invention can be vulcanized more effectively by using a vulcanization accelerator in combination with the vulcanizing agent. The type of vulcanization accelerator that can be blended in the compound composition according to the present invention is not particularly limited as long as it does not impair the effects of the present invention, and one or more vulcanization accelerators generally used in the vulcanization of chloroprene rubber can be freely selected and used. Examples of the vulcanization accelerator include thiuram-based, dithiocarbamate-based, thiourea-based, guanidine-based, xanthogenate-based, and thiazole-based accelerators, which are used alone or in combination of two or more types as necessary. Examples of the thiuram-based vulcanization accelerator include tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, tetrakis(2-ethylhexyl)thiuram disulfide, tetramethylthiuram monosulfide, and dipentamethylenethiuram tetrasulfide. Examples of the dithiocarbamate-based vulcanization accelerator include sodium dibutyldithiocarbamate, zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc N-ethyl-N-phenyldithiocarbamate, zinc N-pentamethylenedithiocarbamate, copper dimethyldithiocarbamate, ferric dimethyldithiocarbamate, and tellurium diethyldithiocarbamate, and zinc dibutyldithiocarbamate is particularly preferred. Examples of the thiourea-based vulcanization accelerator include ethylene thiourea, N,N'-diethyl thiourea, trimethyl thiourea, and N,N'-diphenyl thiourea. Examples of the guanidine-based vulcanization accelerator include 1,3-diphenylguanidine, 1,3-di-o-tolylguanidine, 1-o-tolylbiguanide, and di-o-tolylguanidine salts of dicatechol borate. Examples of the xanthogenate-based vulcanization accelerator include zinc butylxanthogenate and zinc isopropylxanthogenate. Examples of the thiazole-based vulcanization accelerator include 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, 2-mercaptobenzothiazole zinc salt, cyclohexylamine salt of 2-mercaptobenzothiazole, and 2-(4'-morpholinodithio)benzothiazole. In the compound composition according to one embodiment of the present invention, the amount of the vulcanization accelerator added is preferably 0.5 to 5 parts by mass based on 100 parts by mass of the chloroprene polymer.

[0051] <Fillers or reinforcing agents> The filler or reinforcing agent is added to adjust the hardness of the rubber or to improve the mechanical strength, and is not particularly limited, but examples thereof include carbon black, silica, clay, talc, and calcium carbonate. These fillers may be used alone or in combination of two or more. The amounts of these fillers and reinforcing agents added may be adjusted depending on the physical properties required for the rubber composition and the crosslinked rubber or vulcanized rubber obtained from the rubber composition, and are not particularly limited. Generally, the fillers and reinforcing agents can be added in a total amount of 15 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the chloroprene polymer in the compound composition of the present embodiment.

[0052] <Anti-aging agent> The primary antioxidant is mainly blended to suppress the decrease in hardness, elongation at break, etc., when the vulcanized molded product is heated, and to improve heat resistance, and includes phenol-based antioxidants, amine-based antioxidants, acrylate-based antioxidants, carbamic acid metal salts, and waxes. These primary antioxidants can be used alone or in combination. Among these compounds, the amine-based antioxidants 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, octylated diphenylamine, and N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine are preferred because they have a large effect of improving heat resistance.

[0053] The amount of the primary antioxidant is 0.1 to 10 parts by mass, preferably 1 to 5 parts by mass, based on 100 parts by mass of the chloroprene polymer contained in the compound composition. By setting the amount of the primary antioxidant within this range, the hardness and elongation at break of the obtained vulcanized molded product and compound can be prevented from decreasing, and the heat resistance can be improved.

[0054] The secondary antioxidant is mainly used to suppress the decrease in hardness, elongation at break, and compression set when the vulcanized molded product or compound obtained is heated, and to improve heat resistance. Examples of the secondary antioxidant include phosphorus-based antioxidants, sulfur-based antioxidants, and imidazole-based antioxidants. These secondary antioxidants can be used alone or in combination. Among these compounds, phosphorus-based antioxidants such as tris(nonylphenyl)phosphite and tris(2,4-di-t-butylphenyl)phosphite, sulfur-based antioxidants such as diarylthiodipropionate, dimyristyl-3,3'-thiodipropionate, and distearyl-3,3'-thiodipropionate, and imidazole-based antioxidants such as 2-mercaptobenzimidazole and 1-benzyl-2-ethylimidazole are preferred because they have a large effect of improving heat resistance.

[0055] The amount of the secondary antioxidant is 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the chloroprene polymer in the compound composition. By setting the amount of the secondary antioxidant within this range, heat resistance can be improved.

[0056] <Plasticizer> The compound composition according to one embodiment of the present invention may contain a plasticizer. The plasticizer is not particularly limited as long as it is compatible with the chloroprene polymer, and examples thereof include vegetable oils such as rapeseed oil, phthalate plasticizers, DUP (diundecyl phthalate), DOS (dioctyl sebacate), DOA (dioctyl adipate), ester plasticizers, ether ester plasticizers, thioether plasticizers, aromatic oils, and naphthenic oils, and one or more of these may be used in combination according to the properties required for the compound composition. The amount of the plasticizer to be added is preferably 5 to 50 parts by mass relative to 100 parts by mass of the chloroprene polymer.

[0057] <Processing aids> The compound composition according to one embodiment of the present invention may contain a processing aid. The processing aid is mainly added to improve processing characteristics, such as making the compound composition easier to peel off from rolls, molding dies, extruder screws, etc. Examples of the processing aid include fatty acids such as stearic acid and paraffin-based processing aids such as polyethylene, and the like, and it is preferable to add 0.1 to 5 parts by mass of the processing aid to 100 parts by mass of the chloroprene-based polymer.

[0058] <Method of manufacturing compound composition> The compound composition according to one embodiment of the present invention is obtained by kneading a chloroprene polymer or a chloroprene polymer latex and other necessary components at a temperature equal to or lower than the vulcanization temperature. Examples of a device for kneading the raw material components include a conventional kneading device such as a mixer, a Banbury mixer, a kneader mixer, and an open roll.

[0059] <Vulcanized molded body> The vulcanized molded article according to one embodiment of the present invention is a vulcanized molded article obtained by vulcanizing the above-mentioned compound composition. The above-mentioned compound composition may be molded into various desired shapes and then vulcanized, or the compound composition may be made into a vulcanized rubber in advance and then molded into various shapes. Methods for molding the compound composition or vulcanized rubber include conventional methods such as press molding, extrusion molding, and calendar molding. These may be methods commonly used in the rubber industry.

[0060] In the vulcanized molded article according to one embodiment of the present invention, preferably no cracks are generated even after 1.6 million bending cycles, more preferably no cracks are generated even after 1.8 million bending cycles, and even more preferably no cracks are generated even after 2 million bending cycles in the De Mattia bending fatigue test of JIS K6260. The bending test can be carried out by the method described in the Examples.

[0061] The compound composition can be vulcanized by any method, but can be vulcanized by general steam vulcanization or UHF vulcanization. Steam vulcanization is a method of vulcanizing an unvulcanized compound composition by applying pressure and temperature with steam gas as a heat medium, and UHF vulcanization is a method of vulcanizing a compound composition by irradiating microwaves. In addition, the compound composition may be vulcanized by increasing the mold temperature to the vulcanization temperature while holding it inside the mold during press vulcanization or injection molding. The vulcanization temperature can be appropriately set depending on the compounding of the compound composition and the type of vulcanizing agent, and is usually preferably 140 to 220 ° C, more preferably 150 to 180 ° C. The vulcanization time can be, for example, 10 to 30 minutes. The vulcanized rubber is particularly suitable for use in compounds, belts, parts for overhead vehicles, seismic isolation rubber, hoses, wipers, immersion products, seal parts, boots, rubber-coated cloth, rubber rolls, or sponge products. EXAMPLES

[0062] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0063] Example 1 In a reactor having an internal volume of 5 liters, 0.2 parts of n-dodecyl mercaptan, 1.6 parts of potassium rosinate (disproportionated tall rosin potassium salt, manufacturer: Harima Chemicals Co., Ltd.), 0.2 parts of sodium hydroxide, 0.4 parts of sodium salt of formaldehyde naphthalene sulfonic acid condensate (product name: Demol NL, manufacturer: Kao Corporation), and 100 parts of pure water were added relative to 100 parts of chloroprene monomer. 0.05 parts of potassium persulfate was added as a polymerization initiator, and polymerization was carried out under a nitrogen gas flow at a polymerization temperature of 35°C. When the polymerization conversion rate reached 65% or more, 0.01 parts of thiodiphenylamine was added as a polymerization terminator to terminate the reaction. Unreacted monomers were removed under reduced pressure to obtain a chloroprene polymer latex with a solid content of 40%.

[0064] (Examples 2 to 3, Comparative Examples 1 to 3) A chloroprene polymer latex was obtained by the method described in the Examples except that the amount of rosin acid and the total amount of sodium hydroxide and potassium hydroxide were as shown in Table 1.

[0065] <Amount of Rosin Acid in Solid Content Containing Chloroprene Polymer> 3 g of solid matter containing chloroprene polymer obtained by freeze-drying chloroprene polymer latex was cut into 2 mm squares and placed in a recovery flask equipped with a condenser. Rosin acids were extracted with an ethanol-toluene azeotropic mixture (ethanol / toluene volume ratio 7 / 3 (ETA)) and measured by gas chromatography. The rosin acid content was calculated from the peak area of ​​the rosin component. The results are shown in Table 1.

[0066] The gas chromatography was carried out under the following measurement conditions. Column used: FFAP 0.32mmφ×25m (film thickness 0.3μm) Column temperature: 200℃→250℃ Heating rate: 10℃ / min ·Inlet temperature: 270℃ Detector temperature: 270℃ ·Injection volume: 2μL

[0067] <Amount of alkali metal cations in chloroprene polymer latex> 1.0 g of the obtained chloroprene polymer latex was decomposed with sulfuric acid and nitric acid, and then acidified with hydrochloric acid, and the potassium ions and sodium ions were quantified using an inductively coupled plasma atomic emission spectrometer (ICP-AES: VISTA-PRO) manufactured by SII NanoTechnology, Inc. The results are shown in Table 1.

[0068] <Nuclear magnetic resonance analysis of chloroprene polymers( 1 H-NMR) spectrum measurement The chloroprene polymer latex was purified with benzene and methanol, freeze-dried, dissolved in a 5% deuterated chloroform solution, and analyzed by a JNM-ECX-400 (400 MHz, FT type) manufactured by JEOL Ltd. 1The H-NMR spectrum was measured. 1 In the H-NMR spectrum, the peak area A from 5.80 to 6.00 ppm, the peak area B from 4.05 to 6.10 ppm, the peak area C from 4.15 to 4.20 ppm, and the peak area D from 5.40 to 5.60 ppm were measured based on the peak of chloroform in deuterated chloroform (7.24 ppm), and A / B, C / B, and D / B were calculated. The results are shown in Table 1.

[0069] Nuclear magnetic resonance analysis ( 1 The measurement conditions for H-NMR are as follows. Measurement mode: Non-decoupling Flip angle: 45 degrees Latency: 4.3 seconds Sample rotation speed: 0 to 12 Hz Windowing: Exponential Accumulation count: 512 ·Measurement temperature: 30℃

[0070] <Preparation of compound composition and vulcanized molded product> The chloroprene polymer obtained by drying up the above chloroprene polymer latex in a conventional manner and other components were separated according to the formulations shown in Table 1, mixed using an 8-inch roll, and press-crosslinked at 160°C for 20 minutes to prepare a vulcanized molded product having a thickness of 2 mm.

[0071] <Dematcha bending fatigue test> The fatigue durability of the obtained vulcanized molded bodies was evaluated by checking the number of flex tests (unit: 10,000 times) at which cracks occurred under conditions of a stroke of 58 mm and a speed of 300±10 rpm in accordance with the De Mattia flex fatigue test of JIS K6260.

[0072] [Table 1]

Claims

1. Measured in deuterated chloroform solvent 1 In the H-NMR spectrum, It has a peak at 5.80 to 6.00 ppm, When the peak area A is from 5.80 to 6.00 ppm and the peak area B is from 4.05 to 6.10 ppm, A / B is 1.20 / 100 or less, It has a peak at 5.40 to 5.60 ppm, When the peak area from 5.40 to 5.60 ppm is defined as D and the peak area from 4.05 to 6.10 ppm is defined as B, D / B is 97.20 / 100 or less; It has a peak at 4.15 to 4.20 ppm, When the peak area from 4.15 to 4.20 ppm is defined as C and the peak area from 4.05 to 6.10 ppm is defined as B, C / B is 0.10 / 100 or more. Chloroprene polymer.

2. The chloroprene polymer according to claim 1, which is for use in a vulcanized molded product.

3. A chloroprene polymer latex comprising the chloroprene polymer according to claim 1 or 2, the amount of alkali metal cations in the chloroprene polymer latex per unit mass is 0.05 to 0.12 mmol / g, The chloroprene polymer latex is characterized in that, among the solid components containing a chloroprene polymer obtained by freeze-drying the chloroprene polymer latex, an ethanol-toluene azeotropic mixture soluble component defined in JIS K 6229 is extracted under reflux, the extract obtained is treated with hydrochloric acid, and then the amount of rosin acid measured by gas chromatography is 1.4 to 3.2% by mass relative to 100% by mass of the chloroprene polymer.

4. A method for producing the chloroprene polymer latex according to claim 3, comprising the steps of: The method includes an emulsion polymerization step of emulsion-polymerizing a monomer including a chloroprene monomer, In the emulsion polymerization step, using 1.2 to 2.2 parts by mass of a rosin acid salt per 100 parts by mass of the total of the chloroprene monomer and the monomer copolymerizable with chloroprene; A total amount of sodium hydroxide and potassium hydroxide is 0.1 to 0.5 parts by mass per 100 parts by mass of the aqueous medium. A method for producing a chloroprene polymer latex.

5. A compound composition comprising the chloroprene polymer according to claim 1 or 2.

6. A vulcanized molded article comprising the compound composition according to claim 5.

Citation Information

Patent Citations

  • Preparation of chloroprene rubber

    JP1983219206A

  • Production of chloroprene rubber

    JP1996269116A

  • Chloroprene-based polymer composition, method for its production, and adhesive using the composition

    JP2008231404A

  • Chloroprene-based polymer composition, method for producing the same, and adhesive composition

    JP2009191235A

  • Chloroprene polymer composition, and method for producing the same

    JP2013177504A